2013
DOI: 10.1089/neu.2013.2897
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Diffusion Tensor Imaging of Spinal Cord Injury in Rats of Varying Degrees of Severity

Abstract: The aim of this study was to characterize magnetic resonance diffusion tensor imaging (DTI) in proximal regions of the spinal cord following a thoracic spinal cord injury (SCI). Sprague-Dawley rats (n = 40) were administered a control, mild, moderate, or severe contusion injury at the T8 vertebral level. Six direction diffusion weighted images (DWIs) were collected ex vivo along the length of the spinal cord, with an echo/repetition time of 31.6 ms/14 sec and b = 500 sec/mm 2 . Diffusion metrics were correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
44
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 47 publications
11
44
0
Order By: Relevance
“…It is possible that Wallerian degeneration alters membrane structures of the brain and that relative changes in intracellular and extracellular water compartments associated with edema may contribute to changes in diffusion. 8 Our study demonstrated a decrease in the diffusion of water in regions of the brainstem associated with the corticospinal tract along with a corresponding increase in the fractional anisotropy. These observations are consistent with an extension of diffusivity changes from the spinal cord into the white matter tracts of the brainstem and brain.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…It is possible that Wallerian degeneration alters membrane structures of the brain and that relative changes in intracellular and extracellular water compartments associated with edema may contribute to changes in diffusion. 8 Our study demonstrated a decrease in the diffusion of water in regions of the brainstem associated with the corticospinal tract along with a corresponding increase in the fractional anisotropy. These observations are consistent with an extension of diffusivity changes from the spinal cord into the white matter tracts of the brainstem and brain.…”
Section: Discussionsupporting
confidence: 50%
“…19 Recently, we have found that there are systemic changes in DTI parameters that occur along the entire length of the spinal cord following an SCI, 20 and that DTI parameter changes correlate to severity of injury up to 10 weeks. 8 Ten weeks has also been used as a time point by other groups. 18,21 At 10 weeks, the initial acute and inflammatory responses have passed; however, inflammatory cells have been found at locations away from the injury site [22][23][24][25] into regions as far from the injury as the brain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations